DETERMINAN NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Erni Puji Astutik; Rima Parawati Bala; Suci Eriesty Putry (STIE Atma Bhakti, 2018)
The purpose of this research is to examine the effect of Profitability, corporate governance (board size) and Capital Structure to Price to book value (PBV) which is a measurement of company value. This study uses Ordinary Least Square (OLS) test. The sample used is a non-financial company in Indonesia Stock Exchange in 2012 until 2016. Variables tested in this research is the development of variables used by Sri Hermuningsih, (2013). Company value is used as a dependent variable. The result of this research mentioned that there is a positive and significant correlation between variable net profit margin (Profitability) to company value, while for capital structure variable and board size have negative relation and insignificant with company value. Keywords: corporate value, corporate governance, profitability, capital structure.